New developments during the COVID-19 pandemic: Drama therapy as an online psychological intervention tool - Shi, Zhongyu; Jing, Xiuming (Frontiers in Psychology, 2022)
The COVID-19 pandemic has caused many art therapists and psychotherapists to change their practice modes and workplace setup. As a creative arts therapy (CAT), drama therapy has also shifted to an online mode—a shift that has been highly consequential for practice. This paper reviews the existing practice of tele-CAT and tele-drama therapy, explores the advantages and disadvantages of online drama therapy as a psychological intervention tool, and puts forward some developmental suggestions for online drama therapy.